EFL Tertiary Lecturer’s Perception of Integrating YouTube in Teaching Speaking - Sarianti, Sarianti; Maulina, Maulina; Nasrullah, Rahmat (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study was conducted to investigate EFL Tertiary Lecturers' Perceptions of YouTube Integration in English Language Teaching with a focus on the future use of YouTube in Speaking Instruction, The purpose of this study is to find out the perceptions of EFL lecturers in integrating YouTube into their English Language Teaching. This study used a qualitative approach with thematic analysis data collection techniques derived from semi-structured interviews and questionnaires. Based on the research findings, show that lecturers have a positive perception of the use of YouTube to teach speaking, as it is accessible, cost-free, and adaptable. Its diverse content, link-sharing feature, and ability to be accessed from anywhere enhance the learning experience. YouTube also increases student engagement and makes learning more enjoyable. However, lecturers still play a crucial role in bridging theoretical and practical learning. The selection of educational videos must consider duration and relevance to align with learning objectives. Overall, YouTube is a valuable tool in language learning, but its effectiveness is maximized when combined with well-structured guidance from lecturers.